Neuronal somatic plasmalemmal permeability and dendritic beading caused by head rotational traumatic brain injury in pigs–An exploratory study - Harris, James P.; Mietus, Constance J.; Browne, Kevin D.; Wofford, Kathryn L.; Keating, Carolyn E.; Brown, Daniel P.; Johnson, Brian N.; Wolf, John A.; Smith, Douglas H.; Cohen, Akiva S.; Duda, John E.; Cullen, D. Kacy (Frontiers in Cellular Neuroscience, 2023)
Closed-head traumatic brain injury (TBI) is induced by rapid motion of the head, resulting in diffuse strain fields throughout the brain. The injury mechanism(s), loading thresholds, and neuroanatomical distribution of affected cells remain poorly understood, especially in the gyrencephalic brain. We utilized a porcine model to explore the relationships between rapid head rotational acceleration-deceleration loading and immediate alterations in plasmalemmal permeability within cerebral cortex, sub-cortical white matter, and hippocampus. To assess plasmalemmal compromise, Lucifer yellow (LY), a small cell-impermeant dye, was delivered intraventricularly and diffused throughout the parenchyma prior to injury in animals euthanized at 15-min post-injury; other animals (not receiving LY) were survived to 8-h or 7-days. Plasmalemmal permeability preferentially occurred in neuronal somata and dendrites, but rarely in white matter axons. The burden of LY+ neurons increased based on head rotational kinematics, specifically maximum angular velocity, and was exacerbated by repeated TBI. In the cortex, LY+ cells were prominent in both the medial and lateral gyri. Neuronal membrane permeability was observed within the hippocampus and entorhinal cortex, including morphological changes such as beading in dendrites. These changes correlated with reduced fiber volleys and synaptic current alterations at later timepoints in the hippocampus. Further histological observations found decreased NeuN immunoreactivity, increased mitochondrial fission, and caspase pathway activation in both LY+ and LY– cells, suggesting the presence of multiple injury phenotypes. This exploratory study suggests relationships between plasmalemmal disruptions in neuronal somata and dendrites within cortical and hippocampal gray matter as a primary response in closed-head rotational TBI and sets the stage for future, traditional hypothesis-testing experiments.